2021
DOI: 10.3389/fnhum.2021.678472
|View full text |Cite
|
Sign up to set email alerts
|

Previous History of Migraine Is Associated With Fatigue, but Not Headache, as Long-Term Post-COVID Symptom After Severe Acute Respiratory SARS-CoV-2 Infection: A Case-Control Study

Abstract: ObjectiveTo investigate the association of pre-existing migraine in patients hospitalised and who recovered from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with the presence of post-coronavirus disease (COVID) symptoms.BackgroundNo study has investigated the role of migraine as a risk factor for development of post-COVID symptoms.MethodsA case-control study including individuals hospitalised during the first wave of the pandemic (from February 20 to May 31, 2020) was conducted. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…An important finding was that the presence of headache as a COVID‐19 onset symptom but not a history of migraine before the infection was associated with development of post‐COVID‐19 headache in patients infected with the Wuhan or Delta variants, in agreement with some studies. 5 , 16 Accordingly, monitoring headache at the acute phase of SARS‐CoV‐2 infection may alert clinicians of a systemic inflammatory response and potential development of post‐COVID‐19 headache. Interestingly, no difference in the clinical pattern of headache among the three SARS‐CoV‐2 variants was found, because it consistently took on features similar to migraine or tension‐type headache, as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…An important finding was that the presence of headache as a COVID‐19 onset symptom but not a history of migraine before the infection was associated with development of post‐COVID‐19 headache in patients infected with the Wuhan or Delta variants, in agreement with some studies. 5 , 16 Accordingly, monitoring headache at the acute phase of SARS‐CoV‐2 infection may alert clinicians of a systemic inflammatory response and potential development of post‐COVID‐19 headache. Interestingly, no difference in the clinical pattern of headache among the three SARS‐CoV‐2 variants was found, because it consistently took on features similar to migraine or tension‐type headache, as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In that sample, prior history of migraine was also associated with post-COVID headache (OR: 2.90; 95% CI: 1.41–5.98) [ 25 , 26 ]. These data have been previously explored in a smaller sample from the same cohort, that evaluated 57 patients with confirmed diagnosis of migraine prior to the COVID infection and 144 age-and-sex matched controls, where no significant differences were observed regarding anxiety or depression during long COVID evaluated with the Hospital Anxiety and Depression Scale (HADS), but with a higher frequency of post-COVID symptoms (OR: 1.50; 95% CI: 1.09–2.09) [ 27 ]. Another case–control study observed that patients with prior history of migraine had 40% more frequent long-lasting headache, as defined by continuous headache present for more than 1 day [ 28 ].…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%
“…In another study, which assessed patients who had been discharged from the hospital after a mean period of 7 months, the diagnosis of previous migraine was not associated with the persistence of headache. 52 However, previous primary headaches may become worse after COVID‐19. 23 , 34 …”
Section: The Persistence Of Headache After the Acute Phase Of Covid‐19mentioning
confidence: 99%